SUVA PLANINA AS DEVELOPMENT AREA OF RURAL TOURISM - Novica Ranđelović; Vidoje Stefanović; Nedžad Azemović (Ekonomika Poljoprivrede (1979), 2012)
In this paper, an attempt was made to emphasize the importance of the phenomenon of rural tourism once again providing the example of the Suva Planina (The Suva Mountain) since rural tourism is increasingly attracting the attention of potential tourists because they see in it the compensation of what they lose in big agglomerations. The Suva Planina has many attributes to develop this type of tourism and thus to enrich the tourist offer of city of Niš and its environment. The aim is to prove that the Suva Planina mountain area may be an important factor in the development of rural tourism. In proving the hypothesis that the initial development of rural tourism should be accelerated as soon as possible, we used inductive-deductive method and the method of comparison and description. Measures are proposed in order to achieve faster development of rural tourism in this region.